PERBANDINGAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA YANG BELAJAR DENGAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE DAN TIPE THINK PAIR SHARE DI SMP NEGERI 3 PERCUT SEI TUAN - Nuraini . .; Edy . Surya (INSPIRATIF : JURNAL PENDIDIKAN MATEMATIKA, 2017)
ABSTRACT This study aims to determine whether the mathematical communication skills of students who learn by using cooperative learning model Think Talk Write type is higher than the mathematical communication ability of students who learn by using cooperative learning model Think Pair Share type. This type of research is a quasi experiment. The population of this research is all students of class VII of SMP Negeri 3 Percut Sei Tuan. Research sampling was done by cluster sampling and many samples in this research consist of 2 classes, first class is called experimental class I and second class is called experiment class II. The instrument used in this research is a test of mathematical communication ability consisting of 4 items of description. From result of data processing obtained on result of posttest mean score of mathematical communication ability of student 13,4722 for experiment class I and 12,0556 for experiment class II. Based on hypothesis testing that is done by using t test with obtained. This shows that being out of acceptance then based on the test obtained that rejected so it can be stated that the mathematical communication skills of students who learn by using cooperative learning model Think Talk Write type higher than the mathematical communication skills of students who learn by using cooperative learning model type Think Pair Share at SMP Negeri 3 Percut Sei Tuan. Keywords: Mathematical Communication, Think Talk Write, Think Pair Share